Pragmatic Awareness of English Conversational Implicatures among Yemeni-Arabic EFL College Learners - Haifa Mohammad Nassar (Hasanuddin University, 2019)
Conversational implicatures are considered as a tool of indirect communication. Through the researcher 's teaching experience, it has been noticed that Yemeni Arabic EFL College learners are not sufficiently aware of the rules of the use of English and that often words and expressions convey messages above and beyond their literal meanings. This study examined the perception of English conversational implicatures among those learners. The method applied in this study was empirical analytical descriptive with a test and an interview. The subjects were 62 Yemeni Arabic EFL learners. A multiple choice discourse completion test and interview were used for collecting the study data. All the implicatures included in the test were taken from the study related literature, wheras most of test scenarios containing these implicatures were ready -made ones that the researcher came across throughout her reading. The test contains seven types of conversational implicature : Overstatement, Deliberate Ambiguity, Assertion, Indirect Refusal, Disapproval, Indirect Criticism and Indirect Requests. The results showed that Yemeni Arabic EFL College learners do face challenges in relation to the interpretation of these seven conversational implicatures.